Etika Islam: Telaah buku “Antara Al-Ghazali dan Kant: Filsafat Etika Islam” - Abbas, Faiz Musthofa (Universitas Islam Negeri Raden Intan Lampung, 2024)
Abstract;This article is a critical review of a book entitled